Pemberdayaan Keluarga dan Komunitas Dalam Upaya Penanganan Stunting Pada Balita Melalui Pendekatan Sosio Ekologis - Agustina Abuk Seran; Bringiwatty Batbual; Matje Meriaty Huru; Nurlaelah Al-Tadom; Maria Florentina Nining Kosad; Ni Luh Made Diah Putri Anggraeningsih; Odi Lodia Namangdjabar (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2026)
Stunting is a public health problem that is still a national priority because it impacts growth, cognitive development, and the quality of human resources. Handling stunting requires a comprehensive approach involving families, communities, health workers, and the government. The Socioecological Model approach is a strategy that is able to integrate various levels of influence on health behavior, so that it is hoped that it can increase the effectiveness of preventing and treating stunting. This activity aims to increase knowledge, skills, and participation of families and communities in efforts to handle stunting in toddlers through the Socioecological Model approach in East Penfui Village. The activity method is carried out using the community empowerment method, which includes three stages, namely planning, implementation, and evaluation. The planning stage is carried out through coordination with the village government, Community Health Center, Posyandu cadres, and community leaders, as well as identifying community needs. The implementation phase includes counseling about stunting, training for Posyandu cadres, demonstrations on preparing nutritious menus based on local food, family assistance, group discussions, and practice of anthropometric measurements. The evaluation stage was carried out using pre-test and post-test, observing participant skills, as well as monitoring family and cadre participation. The evaluation results show an increase in family knowledge and skills regarding stunting prevention, infant and child feeding practices, and the use of nutritious local food. Posyandu cadres also experienced increased capacity in carrying out early detection of stunting and anthropometric measurements according to standards. Apart from that, there is better collaboration between families, Posyandu cadres, Community Health Centers, and village governments to support sustainable stunting prevention efforts.